Criminalization as Anxious and Ineffective Response to Foreign Fighters Phenomenon in the Western Balkans - Glušac, Luka (Journal of Regional Security, 2020)
Despite not being a new phenomenon, nor an Islamic specifficum, only recently when the West has increasingly become a potential target of returning foreign fighters from the Syrian theater has the international community reacted. e UN Security Council called on Mem- ber-states to, inter alia, immediately amend their national legislation to criminalize travelling abroad for terrorist purposes. However, as I identify in this article, contrary to majority of the Western countries, the Western Balkan countries opted to amend their legislation to criminalize travelling abroad to join confict irrespective of its connection with terrorism, going well beyond the intended aim of the Security Council’s resolutions. I argue that this broader criminal law approach is di cult to justify from either preventive or reactive perspectives. It is, in fact, an anxious and ineffective response to foreign fighters phenomenon. It is anxious because exist- ing data shows that countries from the region have suffered fewer extremist attacks than the West. Notwithstanding, they still decided to introduce far more aggressive legislative changes, even though it only amplified securitizing moves performed by fighters` recruiters. I further demonstrate that the implementation of this new legislation has been ineffective particularly due to: (1) the challenge of securing court-strong evidence, especially those gathered through international intelligence cooperation; (2) its application mainly as an alternative when other terrorism-related offences cannot be proved; and (3) biased law application in countries that have returning fighters from both Middle East and Ukraine.
Keywords: foreign fighters; criminalization; Western Balkans; intelligence; extremism; securitization